Strengthening Data Governance Frameworks for Enhanced Data Quality and Organizational Value Creation - Devang Joshi (Journal of Computational Analysis and Applications (JoCAAA), 2021)
In an era of data-driven decision-making, organizations increasingly recognize data as astrategic asset, yet many struggle to convert large volumes of data into reliable and valuableinsights due to weak governance and poor data quality. This study investigates how strengthening data governance frameworks